The institutional context of tobacco production in Zambia - Ronald Labonté; Raphael Lencucha; Jeffrey Drope; Corinne Packer; Fastone M. Goma; Richard Zulu (BMC, 2018)
Abstract Background Tobacco production is said to be an important contributor to Zambia's economy in terms of labour and revenue generation. In light of Zambia's obligations under the WHO Framework Convention of Tobacco Control (FCTC) we examined the institutional actors in Zambia's tobacco sector to better understand their roles and determine the institutional context that supports tobacco production in Zambia. Methods Findings from 26 qualitative, semi-structured individual or small-group interviews with key informants from governmental, intergovernmental and non-governmental organisations were analysed, along with data and information from published literature. Results Although Zambia is obligated under the FCTC to take steps to reduce tobacco production, the country's weak economy and strong tobacco interests make it difficult to achieve this goal. Respondents uniformly acknowledged that growing the country's economy and ensuring employment for its citizens are the government's top priorities. Lacklustre coordination and collaboration between the institutional actors, both within and outside government, contributes to an environment that helps sustain tobacco production in the country. A Tobacco Products Control Bill has been under review for a number of years, but with no supply measures included, and with no indication of when or whether it will be passed. Conclusions As with other low-income countries involved in tobacco production, there is inconsistency between Zambia's economic policy to strengthen the country's economy and its FCTC commitment to regulate and control tobacco production. The absence of a whole-of-government approach towards tobacco control has created an institutional context of duelling objectives, with some government ministries working at cross-purposes and tobacco interests left unchecked. With no ultimate coordinating authority, this industry risks being run according to the desire and demands of multinational tobacco companies, with few, if any, checks against them.